Reflective dielectric cavity enhanced emission from hexagonal boron nitride spin defect arrays. - Zeng,X-D; Yang,Y-Z; Guo,N-J; Li,Z-P; Wang,Z-A; Xie,L-K; Yu,S; Meng,Y; Li,Q; Xu,J-S; Liu,W; Wang,Y-T; et al. (Nanoscale, 2023)
Among the various kinds of spin defects in hexagonal boron nitride (hBN), the negatively charged boron vacancy (VB-) spin defect that can be site-specifically generated is undoubtedly a potential candidate for quantum sensing, but its low quantum efficiency restricts its practical applications. Here, we demonstrate a robust enhancement structure called reflective dielectric cavity (RDC) with advantages including easy on-chip integration, convenient processing, low cost and suitable broad-spectrum enhancement for VB- defects. In the experiment, we used a metal reflective layer under the hBN flakes, filled with a transition dielectric layer in the middle, and adjusted the thickness of the dielectric layer to achieve the best coupling between RDC and spin defects in hBN. A remarkable 11-fold enhancement in the fluorescence intensity of VB- spin defects in hBN flakes can be achieved. By designing the metal layer into a waveguide structure, high-contrast optically detected magnetic resonance (ODMR) signal (∼21%) can be obtained. The oxide layer of the RDC can be used as the integrated material to implement secondary processing of micro-nano photonic devices, which means that it can be combined with other enhancement structures to achieve stronger enhancement. This work has guiding significance for realizing the on-chip integration of spin defects in two-dimensional materials.